Comparative Environmental Performance of Steam-Based Sterilization (Celitron ISS) and Incineration for Medical Waste: A Life Cycle Assessment - Mohammad A. Ammar; Osama M. Eshibani (African Journal of Advanced Pure and Applied Sciences, 2025)
The management of medical waste presents significant environmental and public health challenges, particularly in developing countries such as Libya. Traditional incineration, widely used for medical waste disposal, generates toxic emissions and contributes to environmental pollution. This study aims to evaluate the environmental performance of Steam Sterilization and Shredding Technology (Celitron ISS) as an alternative to incineration in Libyan medical waste management. A comparative Life Cycle Assessment (LCA) approach was employed to quantify the environmental impacts associated with both treatment methods, including energy consumption, greenhouse gas emissions, and hazardous waste generation. The results indicate that Celitron ISS significantly reduces harmful emissions and resource consumption compared to conventional incineration, highlighting its potential as a more sustainable and environmentally friendly solution. This study provides valuable insights for policymakers and healthcare institutions in Libya, supporting the adoption of innovative waste management technologies to minimize environmental impacts while maintaining effective medical waste treatment practices.